Olmesartan Improves Hepatic Sinusoidal Remodeling in Mice with Carbon Tetrachloride-Induced Liver Fibrosis. (26th August 2022) - Wu, Ying; Ge, Xue; Wang, Si-Ning; Zhang, Chun-Qing
Abstract : Aim . In mice with liver fibrosis produced by carbon tetrachloride (CCl4 ), the effects of olmesartan on intrahepatic angiogenesis and sinusoidal remodeling will be evaluated. Methods . By injecting CCl4 into the peritoneal cavity, we established a mouse model of liver fibrosis. Using Sirius red and Masson trichrome staining, the extent of liver fibrosis in the animals was determined. Using immunohistochemical labeling and western blotting, the level of α -smooth muscle actin ( α -SMA) expression, a characteristic of hepatic stellate cell activation, was assessed. Electron microscopy was used to determine the effect of olmesartan on hepatic sinusoidal capillarization, and immunohistochemical labeling was used to determine the expression levels of endothelial and basement membrane proteins in mouse liver tissues. Platelet-derived growth factor (PDGF), IL-10, vascular endothelial growth factor (VEGF), and angiotensin II levels in mouse serum were measured by Luminex multifactor analysis and ELISA. Olmesartan's effect on the angiotensin II type 1 receptor (AT1R) and the VEGF receptor (VEGFR) was evaluated using western blotting. Results . Olmesartan reduced CCl4 -induced inflammatory cell infiltration and collagen deposition to alleviate liver fibrosis. α -SMA expression was decreased, and HSC activation was inhibited in mouse liver tissues by olmesartan treatment. In addition, hepatic sinusoidal capillarization was improved under the action of olmesartan. The expression of collagen IV, fibronectin, CD31, and von Willebrand factor (VWF) in the olmesartan group was also markedly downregulated. In fibrotic mice, olmesartan medication decreased the levels of PDGF, VEGF, and angiotensin II, but it increased the level of IL-10. Moreover, olmesartan reduced the expression of VEGFR-1, VEGFR-2, and AT1R relative to CCl4 -induced liver fibrosis. Conclusions . In mice with CCl4 -induced fibrosis, olmesartan lowers angiogenesis and improves hepatic sinusoidal remodeling, according to our findings. By acting on the angiotensin II-AT1R-VEGF axis, this is achieved.